Optimalisasi dan Strategi Peningkatan Produksi Padi Lahan Sawah Baru di Kabupaten Aceh Timur - Rizal Fachlevi; Agussabti Agussabti; Ismayani Ismayani (Universitas Teuku Umar, 2018)
The government has tried to increase rice food production, including through the printing of new rice fields. But new rice fields do not directly provide optimal production, so is the case in East Aceh District. This research was conducted to determine the factors that influence the optimization and strategy of increasing the production of new rice fields in East Aceh District. The results showed that urea fertilizer, potassium fertilizer, manure, pesticides and labor costs had a positive and very strong influence on the optimization of rice production in the new rice field, simultaneously the production variables affect the optimization of rice production in the new rice field, while partially seeds, urea fertilizer, manure costs, and labor costs have a significant influence. The results of the SWOT analysis show that there are 14 strategies to increase rice production in new paddy fields in East Aceh District, and the results of QSPM analysis have 5 priority sequences : 1) Increase human resource extension workers and farmers; 2) Strengthening policies, regulations to support food crop production; 3) Opening new rice fields and intensification programs; 4) Conducting partnerships between farmers, academics, extension agents, government institutions, financial institutions, input providers and supporting institutions; 5) Increasing the role of young people in the food crop production sub-sector.